Training on TEKAR (Caramunting flour) Production as Efforts to Enhance Science Literacy - Fathul Zannah; Arna Purtina; Ade S Permadi (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2024)
PKBM is one of the educational facilities, especially non-formal education, to enhance the knowledge and skills of people studying there. This is done to support the improvement of life skills to enhance living welfare (social and economic), one of which is in the form of scientific literacy skills. This community service activity aims to enhance the scientific literacy skills of students studying at community learning centres or PKBM Harati through training activities in making caramunting flour. The method used in community service starts from the planning stage, activity implementation stage and evaluation. The evaluation was carried out by assessing the literacy skills of the activity participants, namely 20 residents studying PKBM Harati, located in Sampit City, East Kotawaringin, Central Kalimantan, by giving test questions of 10 multiple choice questions and measured quantitatively. The results of the activity show that there has been an increase in the scientific literacy learning outcomes of the activity participants, namely that at the pretest, they got an average score of 35, and at the posttest, they got an average score of 83. These results indicate that the training activities carried out can have a positive impact. Positive because it provides concrete examples regarding the application of scientific literacy skills.